Electro-thermal characteristics of hybrid TiO2-SiO2 nanofluid coolants in an electrically-active system - Wan Ahmad Najmi, Wan Mohamed; Mohd. Azeem, Suhaimi; Irnie Azlin, Zakaria; Wan Azmi, Wan Hamzah (Scientific Research Journal (SRJ), 2021)
hermal management in an electrically-active system is a challenging engineering branch due to the critical requirement for rapid cooling rates with inhibition of electrical discharge. A Polymer Electrolyte Membrane Fuel Cell (PEMFC) is an example of a system that needs both conditions to be critically fulfilled. The use of conventional deionised water with low electrical conductivity as the cooling fluid ensures insignificant electrical potential losses but large thermal capacities can only be achieved with a significant penalty to the PEMFC system size. Formulation of nanofluid coolants has been highly successful for systems working under normal environments, but research towards new nanofluid coolants for active electrical systems are relatively new. This paper reports a fundamental investigation on the electrical and thermal behaviours of a hybrid 1%v TiOz-SiOz(at 50:50 ratio) nanofluid dispersed in 60:40 water/ethylene glycol solution. A test bench consisting of a heated rectangular channel combined with continuous electrical supply at 0.7 V and 3 A nominal current was developed to simulate the operating conditions of a PEMFC stack cooling. The test variables are the heater temperature and Reynolds number (300 to 700) of the coolants. The cooling profiles and changes in electrical properties of the system and coolants were analysed. Significant increase in cooling rates were achieved by the hybrid nanofluids (200% to 250%) compared to water and water/ethylene glycol coolants. The electrica analysis indicates that the power drop is low for water and water/ethylene glycol but drops rapidly in an exponential profile (between 15% to 45%) which also leads to a visible increase in the electrical conductivity of the nanofluids coolants. As such, further research is needed to reduce the apparent electrical discharge problem before a suitable nanofluid coolant can be developed for electrically-active systems.